NEGATIVE REGULATION OF MOENOMYCIN A BIOSYNTHESIS IN STREPTOMYCES GHANAENSIS ATCC14672 - К. С. Маракасова; Б. О. Осташ; В. О. Федоренко (Mìkrobìologìâ ì Bìotehnologìâ. Мікробіологія і біотехнологія, 2009)
Members of the soil-dwelling prokaryotic genus streptomyces produce around twothirds of all known antibiotics. Moenomycin A is a potent antibacterial drug against many Gram-positive pathogens, including vancomycin-resistant pathogens. studying of moenomycin A biosynthesis regulation is of great importance because of need of new tools for combinatorial biosynthesis. In this work we examined the effects of known pleiotropic regulator DasR on moenomycin biosynthesis under heterologous conditions. DasR controls several pivotal cellular processes, including the transport of N-acetylglucosamine (GlcNAc), ubiquitous metabolite and an important source of carbon and nitrogen in soil ecosystems. Gene dasR was inactivated ins. coelicolor and moenomycin biosynthetic gene cluster was expressed in the mutant and parent strains. Moenomycin production increased twofold in dasR-deficient strain, confirming the involvement of DasR in regulation of phosphoglycolipid production.